Earlywood vessel features in Quercus faginea: relationship between ring width and wood density at two sites in Portugal - Sousa, Vicelina B. (2017)
Wood anatomy holds relevant information for tree development and timber quality (e.g., wood density), which is important for the sustainability of the species. Quercus faginea Lam. (Portuguese or Lusitanian oak) is an autochthonous Mediterranean oak species characterized by a shrinking natural distribution area and use abandonment. We studied the variation of several wood properties and their relationships with the aim of determining and possibly increasing the wood economic value of this species. The anatomical features of earlywood vessels (area, number, frequency and proportion) were investigated in twenty Q. faginea trees sampled at two locations within the natural distribution of the species in Portugal. Moreover, we analyzed the variation of vessel features from pith to bark, the radial growth and the wood density to search for patterns and relationships among the analyzed parameters. Mean earlywood vessel area increased with cambial age up to 60-70 years and then leveled off. An inverse pattern was found for the number of vessels per ring beyond that age. Similar radial patterns of all vessel features were found at both sites, and no significant differences in earlywood vessel area were found between sites. The within-tree development of earlywood vessels was age-related, though not influenced by growth. Earlywood vessel features explained the variation of wood density, i.e., wood density of Q. faginea was strongly negatively correlated with both mean vessel area and proportion